2022
DOI: 10.14742/ajet.7219
|View full text |Cite
|
Sign up to set email alerts
|

Learning technology acceptance and continuance intention among business students: The mediating effects of confirmation, flow, and engagement

Abstract: The emergence of mobile applications has opened the door to a new kind of information and communication technology tool and educational support which is vital for students’ positive learning behaviours. The aims of this study were to examine the effects of three mediators (confirmation, flow, and student engagement) on students’ learning technology acceptance and information systems continuance intention, and to explore the functions of these variables in the mediating process between learning technology accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…This can be explained by the fact that the single dimensional construct we adopted to measure students' engagement did not capture the complexities of engagement in the online learning context precisely enough. Engagement is a dynamic, multi-faceted, and context-dependent construct, and its effects need more investigation in the future [106].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that the single dimensional construct we adopted to measure students' engagement did not capture the complexities of engagement in the online learning context precisely enough. Engagement is a dynamic, multi-faceted, and context-dependent construct, and its effects need more investigation in the future [106].…”
Section: Discussionmentioning
confidence: 99%
“…As declared by Hair et al (2021) moderating variables will render more generalizability of the research findings. The two antecedents of attitudes in the TAM model, however, were neglected in some studies, (i.e., Şahin et al, 2022;Tseng et al, 2022) leading to a misperception that their mediating role in shaping users' intentions towards the target system. Our study will identify them as mediators between learners' online L2 selfidentities and attitudes toward online language learning.…”
Section: Current Study: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Apart from the above-mentioned student characteristics that might affect their choices of course modalities, previous studies have also indicated a potential correlation between students' perceptions of their prior online experience and their choices. (e.g., T. Braun, 2008;Harris & Martin, 2012;Kleisus et al, 1997;Kowalski et al, 2014;Nguyen & Zhang, 2011;Ruffalo, 2016;Thomerson & Smith, 1996;Tseng et al, 2022). Students who have more prior OL experience and felt more satisfied were more likely to choose online courses or courses with online components again (e.g., Artino, 2010;T.…”
Section: The Impact Of Student Characteristics Learning Experiences A...mentioning
confidence: 99%